/- Copyright (c) 2014 Floris van Doorn. All rights reserved. Released under Apache 2.0 license as described in the file LICENSE. Authors: Floris van Doorn, Leonardo de Moura, Jeremy Avigad The order relation on the natural numbers. -/ import .basic algebra.ordered_ring open eq.ops namespace nat /- lt and le -/ protected theorem le_of_lt_or_eq {m n : ℕ} (H : m < n ∨ m = n) : m ≤ n := nat.le_of_eq_or_lt (or.swap H) protected theorem lt_or_eq_of_le {m n : ℕ} (H : m ≤ n) : m < n ∨ m = n := or.swap (nat.eq_or_lt_of_le H) protected theorem le_iff_lt_or_eq (m n : ℕ) : m ≤ n ↔ m < n ∨ m = n := iff.intro nat.lt_or_eq_of_le nat.le_of_lt_or_eq protected theorem lt_of_le_and_ne {m n : ℕ} (H1 : m ≤ n) : m ≠ n → m < n := or_resolve_right (nat.eq_or_lt_of_le H1) protected theorem lt_iff_le_and_ne (m n : ℕ) : m < n ↔ m ≤ n ∧ m ≠ n := iff.intro (take H, and.intro (nat.le_of_lt H) (take H1, !nat.lt_irrefl (H1 ▸ H))) (and.rec nat.lt_of_le_and_ne) theorem le_add_right (n k : ℕ) : n ≤ n + k := nat.rec !nat.le_refl (λ k, le_succ_of_le) k theorem le_add_left (n m : ℕ): n ≤ m + n := !add.comm ▸ !le_add_right theorem le.intro {n m k : ℕ} (h : n + k = m) : n ≤ m := h ▸ !le_add_right theorem le.elim {n m : ℕ} : n ≤ m → ∃ k, n + k = m := le.rec (exists.intro 0 rfl) (λm h, Exists.rec (λ k H, exists.intro (succ k) (H ▸ rfl))) protected theorem le_total {m n : ℕ} : m ≤ n ∨ n ≤ m := or.imp_left nat.le_of_lt !nat.lt_or_ge /- addition -/ protected theorem add_le_add_left {n m : ℕ} (H : n ≤ m) (k : ℕ) : k + n ≤ k + m := obtain l Hl, from le.elim H, le.intro (Hl ▸ !add.assoc) protected theorem add_le_add_right {n m : ℕ} (H : n ≤ m) (k : ℕ) : n + k ≤ m + k := !add.comm ▸ !add.comm ▸ nat.add_le_add_left H k protected theorem le_of_add_le_add_left {k n m : ℕ} (H : k + n ≤ k + m) : n ≤ m := obtain l Hl, from le.elim H, le.intro (nat.add_left_cancel (!add.assoc⁻¹ ⬝ Hl)) protected theorem lt_of_add_lt_add_left {k n m : ℕ} (H : k + n < k + m) : n < m := let H' := nat.le_of_lt H in nat.lt_of_le_and_ne (nat.le_of_add_le_add_left H') (assume Heq, !nat.lt_irrefl (Heq ▸ H)) protected theorem add_lt_add_left {n m : ℕ} (H : n < m) (k : ℕ) : k + n < k + m := lt_of_succ_le (!add_succ ▸ nat.add_le_add_left (succ_le_of_lt H) k) protected theorem add_lt_add_right {n m : ℕ} (H : n < m) (k : ℕ) : n + k < m + k := !add.comm ▸ !add.comm ▸ nat.add_lt_add_left H k protected theorem lt_add_of_pos_right {n k : ℕ} (H : k > 0) : n < n + k := !add_zero ▸ nat.add_lt_add_left H n /- multiplication -/ theorem mul_le_mul_left {n m : ℕ} (k : ℕ) (H : n ≤ m) : k * n ≤ k * m := obtain (l : ℕ) (Hl : n + l = m), from le.elim H, have k * n + k * l = k * m, by rewrite [-left_distrib, Hl], le.intro this theorem mul_le_mul_right {n m : ℕ} (k : ℕ) (H : n ≤ m) : n * k ≤ m * k := !mul.comm ▸ !mul.comm ▸ !mul_le_mul_left H protected theorem mul_le_mul {n m k l : ℕ} (H1 : n ≤ k) (H2 : m ≤ l) : n * m ≤ k * l := nat.le_trans (!nat.mul_le_mul_right H1) (!nat.mul_le_mul_left H2) protected theorem mul_lt_mul_of_pos_left {n m k : ℕ} (H : n < m) (Hk : k > 0) : k * n < k * m := nat.lt_of_lt_of_le (nat.lt_add_of_pos_right Hk) (!mul_succ ▸ nat.mul_le_mul_left k (succ_le_of_lt H)) protected theorem mul_lt_mul_of_pos_right {n m k : ℕ} (H : n < m) (Hk : k > 0) : n * k < m * k := !mul.comm ▸ !mul.comm ▸ nat.mul_lt_mul_of_pos_left H Hk /- nat is an instance of a linearly ordered semiring and a lattice -/ protected definition decidable_linear_ordered_semiring [reducible] [trans_instance] : decidable_linear_ordered_semiring nat := ⦃ decidable_linear_ordered_semiring, nat.comm_semiring, add_left_cancel := @nat.add_left_cancel, add_right_cancel := @nat.add_right_cancel, lt := nat.lt, le := nat.le, le_refl := nat.le_refl, le_trans := @nat.le_trans, le_antisymm := @nat.le_antisymm, le_total := @nat.le_total, le_iff_lt_or_eq := @nat.le_iff_lt_or_eq, le_of_lt := @nat.le_of_lt, lt_irrefl := @nat.lt_irrefl, lt_of_lt_of_le := @nat.lt_of_lt_of_le, lt_of_le_of_lt := @nat.lt_of_le_of_lt, lt_of_add_lt_add_left := @nat.lt_of_add_lt_add_left, add_lt_add_left := @nat.add_lt_add_left, add_le_add_left := @nat.add_le_add_left, le_of_add_le_add_left := @nat.le_of_add_le_add_left, zero_lt_one := zero_lt_succ 0, mul_le_mul_of_nonneg_left := (take a b c H1 H2, nat.mul_le_mul_left c H1), mul_le_mul_of_nonneg_right := (take a b c H1 H2, nat.mul_le_mul_right c H1), mul_lt_mul_of_pos_left := @nat.mul_lt_mul_of_pos_left, mul_lt_mul_of_pos_right := @nat.mul_lt_mul_of_pos_right, decidable_lt := nat.decidable_lt ⦄ definition nat_has_dvd [reducible] [instance] [priority nat.prio] : has_dvd nat := has_dvd.mk has_dvd.dvd theorem add_pos_left {a : ℕ} (H : 0 < a) (b : ℕ) : 0 < a + b := @add_pos_of_pos_of_nonneg _ _ a b H !zero_le theorem add_pos_right {a : ℕ} (H : 0 < a) (b : ℕ) : 0 < b + a := by rewrite add.comm; apply add_pos_left H b theorem add_eq_zero_iff_eq_zero_and_eq_zero {a b : ℕ} : a + b = 0 ↔ a = 0 ∧ b = 0 := @add_eq_zero_iff_eq_zero_and_eq_zero_of_nonneg_of_nonneg _ _ a b !zero_le !zero_le theorem le_add_of_le_left {a b c : ℕ} (H : b ≤ c) : b ≤ a + c := @le_add_of_nonneg_of_le _ _ a b c !zero_le H theorem le_add_of_le_right {a b c : ℕ} (H : b ≤ c) : b ≤ c + a := @le_add_of_le_of_nonneg _ _ a b c H !zero_le theorem lt_add_of_lt_left {b c : ℕ} (H : b < c) (a : ℕ) : b < a + c := @lt_add_of_nonneg_of_lt _ _ a b c !zero_le H theorem lt_add_of_lt_right {b c : ℕ} (H : b < c) (a : ℕ) : b < c + a := @lt_add_of_lt_of_nonneg _ _ a b c H !zero_le theorem lt_of_mul_lt_mul_left {a b c : ℕ} (H : c * a < c * b) : a < b := @lt_of_mul_lt_mul_left _ _ a b c H !zero_le theorem lt_of_mul_lt_mul_right {a b c : ℕ} (H : a * c < b * c) : a < b := @lt_of_mul_lt_mul_right _ _ a b c H !zero_le theorem pos_of_mul_pos_left {a b : ℕ} (H : 0 < a * b) : 0 < b := @pos_of_mul_pos_left _ _ a b H !zero_le theorem pos_of_mul_pos_right {a b : ℕ} (H : 0 < a * b) : 0 < a := @pos_of_mul_pos_right _ _ a b H !zero_le theorem zero_le_one : (0:nat) ≤ 1 := dec_trivial /- properties specific to nat -/ theorem lt_intro {n m k : ℕ} (H : succ n + k = m) : n < m := lt_of_succ_le (le.intro H) theorem lt_elim {n m : ℕ} (H : n < m) : ∃k, succ n + k = m := le.elim (succ_le_of_lt H) theorem lt_add_succ (n m : ℕ) : n < n + succ m := lt_intro !succ_add_eq_succ_add theorem eq_zero_of_le_zero {n : ℕ} (H : n ≤ 0) : n = 0 := obtain (k : ℕ) (Hk : n + k = 0), from le.elim H, eq_zero_of_add_eq_zero_right Hk /- succ and pred -/ theorem le_of_lt_succ {m n : nat} : m < succ n → m ≤ n := le_of_succ_le_succ theorem lt_iff_succ_le (m n : nat) : m < n ↔ succ m ≤ n := iff.rfl theorem lt_succ_iff_le (m n : nat) : m < succ n ↔ m ≤ n := iff.intro le_of_lt_succ lt_succ_of_le theorem self_le_succ (n : ℕ) : n ≤ succ n := le.intro !add_one theorem succ_le_or_eq_of_le {n m : ℕ} : n ≤ m → succ n ≤ m ∨ n = m := lt_or_eq_of_le theorem pred_le_of_le_succ {n m : ℕ} : n ≤ succ m → pred n ≤ m := pred_le_pred theorem succ_le_of_le_pred {n m : ℕ} : succ n ≤ m → n ≤ pred m := pred_le_pred theorem pred_le_pred_of_le {n m : ℕ} : n ≤ m → pred n ≤ pred m := pred_le_pred theorem pre_lt_of_lt {n m : ℕ} : n < m → pred n < m := lt_of_le_of_lt !pred_le theorem lt_of_pred_lt_pred {n m : ℕ} (H : pred n < pred m) : n < m := lt_of_not_ge (suppose m ≤ n, not_lt_of_ge (pred_le_pred_of_le this) H) theorem le_or_eq_succ_of_le_succ {n m : ℕ} (H : n ≤ succ m) : n ≤ m ∨ n = succ m := or.imp_left le_of_succ_le_succ (succ_le_or_eq_of_le H) theorem le_pred_self (n : ℕ) : pred n ≤ n := !pred_le theorem succ_pos (n : ℕ) : 0 < succ n := !zero_lt_succ theorem succ_pred_of_pos {n : ℕ} (H : n > 0) : succ (pred n) = n := (or_resolve_right (eq_zero_or_eq_succ_pred n) (ne.symm (ne_of_lt H)))⁻¹ theorem exists_eq_succ_of_lt {n : ℕ} : Π {m : ℕ}, n < m → ∃k, m = succ k | 0 H := absurd H !not_lt_zero | (succ k) H := exists.intro k rfl theorem lt_succ_self (n : ℕ) : n < succ n := lt.base n lemma lt_succ_of_lt {i j : nat} : i < j → i < succ j := assume Plt, lt.trans Plt (self_lt_succ j) /- other forms of induction -/ protected definition strong_rec_on {P : nat → Type} (n : ℕ) (H : ∀n, (∀m, m < n → P m) → P n) : P n := nat.rec (λm h, absurd h !not_lt_zero) (λn' (IH : ∀ {m : ℕ}, m < n' → P m) m l, or.by_cases (lt_or_eq_of_le (le_of_lt_succ l)) IH (λ e, eq.rec (H n' @IH) e⁻¹)) (succ n) n !lt_succ_self protected theorem strong_induction_on {P : nat → Prop} (n : ℕ) (H : ∀n, (∀m, m < n → P m) → P n) : P n := nat.strong_rec_on n H protected theorem case_strong_induction_on {P : nat → Prop} (a : nat) (H0 : P 0) (Hind : ∀(n : nat), (∀m, m ≤ n → P m) → P (succ n)) : P a := nat.strong_induction_on a (take n, show (∀ m, m < n → P m) → P n, from nat.cases_on n (suppose (∀ m, m < 0 → P m), show P 0, from H0) (take n, suppose (∀ m, m < succ n → P m), show P (succ n), from Hind n (take m, assume H1 : m ≤ n, this _ (lt_succ_of_le H1)))) /- pos -/ theorem by_cases_zero_pos {P : ℕ → Prop} (y : ℕ) (H0 : P 0) (H1 : ∀ {y : nat}, y > 0 → P y) : P y := nat.cases_on y H0 (take y, H1 !succ_pos) theorem eq_zero_or_pos (n : ℕ) : n = 0 ∨ n > 0 := or_of_or_of_imp_left (or.swap (lt_or_eq_of_le !zero_le)) (suppose 0 = n, by subst n) theorem pos_of_ne_zero {n : ℕ} (H : n ≠ 0) : n > 0 := or.elim !eq_zero_or_pos (take H2 : n = 0, by contradiction) (take H2 : n > 0, H2) theorem ne_zero_of_pos {n : ℕ} (H : n > 0) : n ≠ 0 := ne.symm (ne_of_lt H) theorem exists_eq_succ_of_pos {n : ℕ} (H : n > 0) : ∃l, n = succ l := exists_eq_succ_of_lt H theorem pos_of_dvd_of_pos {m n : ℕ} (H1 : m ∣ n) (H2 : n > 0) : m > 0 := pos_of_ne_zero (suppose m = 0, assert n = 0, from eq_zero_of_zero_dvd (this ▸ H1), ne_of_lt H2 (by subst n)) /- multiplication -/ theorem mul_lt_mul_of_le_of_lt {n m k l : ℕ} (Hk : k > 0) (H1 : n ≤ k) (H2 : m < l) : n * m < k * l := lt_of_le_of_lt (mul_le_mul_right m H1) (mul_lt_mul_of_pos_left H2 Hk) theorem mul_lt_mul_of_lt_of_le {n m k l : ℕ} (Hl : l > 0) (H1 : n < k) (H2 : m ≤ l) : n * m < k * l := lt_of_le_of_lt (mul_le_mul_left n H2) (mul_lt_mul_of_pos_right H1 Hl) theorem mul_lt_mul_of_le_of_le {n m k l : ℕ} (H1 : n < k) (H2 : m < l) : n * m < k * l := have H3 : n * m ≤ k * m, from mul_le_mul_right m (le_of_lt H1), have H4 : k * m < k * l, from mul_lt_mul_of_pos_left H2 (lt_of_le_of_lt !zero_le H1), lt_of_le_of_lt H3 H4 theorem eq_of_mul_eq_mul_left {m k n : ℕ} (Hn : n > 0) (H : n * m = n * k) : m = k := have n * m ≤ n * k, by rewrite H, have m ≤ k, from le_of_mul_le_mul_left this Hn, have n * k ≤ n * m, by rewrite H, have k ≤ m, from le_of_mul_le_mul_left this Hn, le.antisymm `m ≤ k` this theorem eq_of_mul_eq_mul_right {n m k : ℕ} (Hm : m > 0) (H : n * m = k * m) : n = k := eq_of_mul_eq_mul_left Hm (!mul.comm ▸ !mul.comm ▸ H) theorem eq_zero_or_eq_of_mul_eq_mul_left {n m k : ℕ} (H : n * m = n * k) : n = 0 ∨ m = k := or_of_or_of_imp_right !eq_zero_or_pos (assume Hn : n > 0, eq_of_mul_eq_mul_left Hn H) theorem eq_zero_or_eq_of_mul_eq_mul_right {n m k : ℕ} (H : n * m = k * m) : m = 0 ∨ n = k := eq_zero_or_eq_of_mul_eq_mul_left (!mul.comm ▸ !mul.comm ▸ H) theorem eq_one_of_mul_eq_one_right {n m : ℕ} (H : n * m = 1) : n = 1 := have H2 : n * m > 0, by rewrite H; apply succ_pos, or.elim (le_or_gt n 1) (suppose n ≤ 1, have n > 0, from pos_of_mul_pos_right H2, show n = 1, from le.antisymm `n ≤ 1` (succ_le_of_lt this)) (suppose n > 1, have m > 0, from pos_of_mul_pos_left H2, have n * m ≥ 2 * 1, from nat.mul_le_mul (succ_le_of_lt `n > 1`) (succ_le_of_lt this), have 1 ≥ 2, from !mul_one ▸ H ▸ this, absurd !lt_succ_self (not_lt_of_ge this)) theorem eq_one_of_mul_eq_one_left {n m : ℕ} (H : n * m = 1) : m = 1 := eq_one_of_mul_eq_one_right (!mul.comm ▸ H) theorem eq_one_of_mul_eq_self_left {n m : ℕ} (Hpos : n > 0) (H : m * n = n) : m = 1 := eq_of_mul_eq_mul_right Hpos (H ⬝ !one_mul⁻¹) theorem eq_one_of_mul_eq_self_right {n m : ℕ} (Hpos : m > 0) (H : m * n = m) : n = 1 := eq_one_of_mul_eq_self_left Hpos (!mul.comm ▸ H) theorem eq_one_of_dvd_one {n : ℕ} (H : n ∣ 1) : n = 1 := dvd.elim H (take m, suppose 1 = n * m, eq_one_of_mul_eq_one_right this⁻¹) /- min and max -/ open decidable theorem min_zero [simp] (a : ℕ) : min a 0 = 0 := by rewrite [min_eq_right !zero_le] theorem zero_min [simp] (a : ℕ) : min 0 a = 0 := by rewrite [min_eq_left !zero_le] theorem max_zero [simp] (a : ℕ) : max a 0 = a := by rewrite [max_eq_left !zero_le] theorem zero_max [simp] (a : ℕ) : max 0 a = a := by rewrite [max_eq_right !zero_le] theorem min_succ_succ [simp] (a b : ℕ) : min (succ a) (succ b) = succ (min a b) := or.elim !lt_or_ge (suppose a < b, by rewrite [min_eq_left_of_lt this, min_eq_left_of_lt (succ_lt_succ this)]) (suppose a ≥ b, by rewrite [min_eq_right this, min_eq_right (succ_le_succ this)]) theorem max_succ_succ [simp] (a b : ℕ) : max (succ a) (succ b) = succ (max a b) := or.elim !lt_or_ge (suppose a < b, by rewrite [max_eq_right_of_lt this, max_eq_right_of_lt (succ_lt_succ this)]) (suppose a ≥ b, by rewrite [max_eq_left this, max_eq_left (succ_le_succ this)]) /- In algebra.ordered_group, these next four are only proved for additive groups, not additive semigroups. -/ protected theorem min_add_add_left (a b c : ℕ) : min (a + b) (a + c) = a + min b c := decidable.by_cases (suppose b ≤ c, assert a + b ≤ a + c, from add_le_add_left this _, by rewrite [min_eq_left `b ≤ c`, min_eq_left this]) (suppose ¬ b ≤ c, assert c ≤ b, from le_of_lt (lt_of_not_ge this), assert a + c ≤ a + b, from add_le_add_left this _, by rewrite [min_eq_right `c ≤ b`, min_eq_right this]) protected theorem min_add_add_right (a b c : ℕ) : min (a + c) (b + c) = min a b + c := by rewrite [add.comm a c, add.comm b c, add.comm _ c]; apply nat.min_add_add_left protected theorem max_add_add_left (a b c : ℕ) : max (a + b) (a + c) = a + max b c := decidable.by_cases (suppose b ≤ c, assert a + b ≤ a + c, from add_le_add_left this _, by rewrite [max_eq_right `b ≤ c`, max_eq_right this]) (suppose ¬ b ≤ c, assert c ≤ b, from le_of_lt (lt_of_not_ge this), assert a + c ≤ a + b, from add_le_add_left this _, by rewrite [max_eq_left `c ≤ b`, max_eq_left this]) protected theorem max_add_add_right (a b c : ℕ) : max (a + c) (b + c) = max a b + c := by rewrite [add.comm a c, add.comm b c, add.comm _ c]; apply nat.max_add_add_left /- least and greatest -/ section least_and_greatest variable (P : ℕ → Prop) variable [decP : ∀ n, decidable (P n)] include decP -- returns the least i < n satisfying P, or n if there is none definition least : ℕ → ℕ | 0 := 0 | (succ n) := if P (least n) then least n else succ n theorem least_of_bound {n : ℕ} (H : P n) : P (least P n) := begin induction n with [m, ih], rewrite ↑least, apply H, rewrite ↑least, cases decidable.em (P (least P m)) with [Hlp, Hlp], rewrite [if_pos Hlp], apply Hlp, rewrite [if_neg Hlp], apply H end theorem least_le (n : ℕ) : least P n ≤ n:= begin induction n with [m, ih], {rewrite ↑least}, rewrite ↑least, cases decidable.em (P (least P m)) with [Psm, Pnsm], rewrite [if_pos Psm], apply le.trans ih !le_succ, rewrite [if_neg Pnsm] end theorem least_of_lt {i n : ℕ} (ltin : i < n) (H : P i) : P (least P n) := begin induction n with [m, ih], exact absurd ltin !not_lt_zero, rewrite ↑least, cases decidable.em (P (least P m)) with [Psm, Pnsm], rewrite [if_pos Psm], apply Psm, rewrite [if_neg Pnsm], cases (lt_or_eq_of_le (le_of_lt_succ ltin)) with [Hlt, Heq], exact absurd (ih Hlt) Pnsm, rewrite Heq at H, exact absurd (least_of_bound P H) Pnsm end theorem ge_least_of_lt {i n : ℕ} (ltin : i < n) (Hi : P i) : i ≥ least P n := begin induction n with [m, ih], exact absurd ltin !not_lt_zero, rewrite ↑least, cases decidable.em (P (least P m)) with [Psm, Pnsm], rewrite [if_pos Psm], cases (lt_or_eq_of_le (le_of_lt_succ ltin)) with [Hlt, Heq], apply ih Hlt, rewrite Heq, apply least_le, rewrite [if_neg Pnsm], cases (lt_or_eq_of_le (le_of_lt_succ ltin)) with [Hlt, Heq], apply absurd (least_of_lt P Hlt Hi) Pnsm, rewrite Heq at Hi, apply absurd (least_of_bound P Hi) Pnsm end theorem least_lt {n i : ℕ} (ltin : i < n) (Hi : P i) : least P n < n := lt_of_le_of_lt (ge_least_of_lt P ltin Hi) ltin -- returns the largest i < n satisfying P, or n if there is none. definition greatest : ℕ → ℕ | 0 := 0 | (succ n) := if P n then n else greatest n theorem greatest_of_lt {i n : ℕ} (ltin : i < n) (Hi : P i) : P (greatest P n) := begin induction n with [m, ih], {exact absurd ltin !not_lt_zero}, {cases (decidable.em (P m)) with [Psm, Pnsm], {rewrite [↑greatest, if_pos Psm]; exact Psm}, {rewrite [↑greatest, if_neg Pnsm], have neim : i ≠ m, from assume H : i = m, absurd (H ▸ Hi) Pnsm, have ltim : i < m, from lt_of_le_of_ne (le_of_lt_succ ltin) neim, apply ih ltim}} end theorem le_greatest_of_lt {i n : ℕ} (ltin : i < n) (Hi : P i) : i ≤ greatest P n := begin induction n with [m, ih], {exact absurd ltin !not_lt_zero}, {cases (decidable.em (P m)) with [Psm, Pnsm], {rewrite [↑greatest, if_pos Psm], apply le_of_lt_succ ltin}, {rewrite [↑greatest, if_neg Pnsm], have neim : i ≠ m, from assume H : i = m, absurd (H ▸ Hi) Pnsm, have ltim : i < m, from lt_of_le_of_ne (le_of_lt_succ ltin) neim, apply ih ltim}} end end least_and_greatest end nat